Asian Brand Strategy (Revised and Updated) Building and Sustaining Strong Global Brands in Asia - Roll, Martin; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This second edition of the bestselling Asian Brand Strategy takes a look at how Asian brands continue to gain share-of-voice and share-of-market. Featuring a user-friendly strategic model, new research, and case studies, this book provides a framework for understanding Asian branding strategies and Asian brands.
Keywords: Business; Marketing; Leadership; International business enterprises; International economics; Asia -- Economic conditions; Business and Management; Business Strategy/Leadership.; Marketing; Asian Economics; International Business; International Economics; Electronic books